Coexistence of different social groups around one of the campuses of the University of Pécs - Makkai, Bernadett; Gyüre, Judit (Journal for Geography, 2012)
In the process of urban transformation and renewal, large numbers of immigrants are expected in connection with the existence of prosperous branches of industry. It is assumed that in an environment where higher education is one of the most important economic factors, there will be conflicts in the everyday coexistence of social groups. The aim of this study is to investigate, in a city quarter which was forced to transform due to economic structural changes, and which has a bold mixture of ageing people and temporary university residents, how the coexistence of different groups of the society influences the quality of life in the quarter, and how the situation is perceived by the affected people themselves. Furthermore, we want to see what kinds of tension arise from the interactions between these groups with dissimilar/different background, and what possible solutions can be found to resolve such tension. V procesu preoblikovanja in prenove mest se pričakuje veliko število priseljencev v povezavi z obstojem uspešnih industrijskih panog. Predvideva se, da bo v okolju, kjer je visokošolska izobrazba eden najpomembnejših gospodarskih dejavnikov, prihajalo do konfliktov v vsakdanjem sobivanju družbenih skupin. Namen te študije je v mestni četrti, ki se je morala preoblikovati zaradi gospodarskih strukturnih sprememb in v kateri se pogumno mešajo starajoči se ljudje in začasni prebivalci univerz, raziskati, kako sobivanje različnih družbenih skupin vpliva na kakovost življenja v četrti in kako razmere zaznavajo prizadeti ljudje sami. Poleg tega želimo ugotoviti, kakšne vrste napetosti nastajajo zaradi interakcij med temi skupinami z različnim/različnim ozadjem in kakšne možne rešitve je mogoče najti za odpravo teh napetosti.